STUDIES ON RADIATION PASTEURISATION OF MEDIUM FATTY FISH II. PRECURSORS OF YELLOW DISCOLOURATION IN IRRADIATED WHITE POMFRET (STROMATEUS CINEREUS) - KUMTA, U S; KAMAT, S V (Fishery Technology, 2025)
Triglycerides, phospholipids and sarcoplasmic proteins fractionsof white pomfret produced considerable amounts of thiobarbituric acidreactive substances (TBRS) on irradiation. Incubation of malonaldehydewith pomfret skin under aseptic conditions developed yellowpigmentation of the skin tissues, similar in spectral characteristics tothose produced on irradiation of the skin.